Do Accruals Earnings Management Constraints and Intellectual Capital Efficiency Trigger Asymmetric Cost Behaviour? Evidence from Australia. Issue 1 (26th June 2018) - Yang, Yiru
Abstract: This study examines whether accruals earnings management constraints and intellectual capital (IC) efficiency affect asymmetric cost behaviour by analysing data for the 1990 to 2016 period on firms listed on the Australian Securities Exchange. The analysis reveals that, on average, anti‐sticky cost behaviour occurs when firms have limited ability to engage in accrual earnings management to manipulate earnings in the current year. Further, IC efficiency – particularly human capital efficiency – increases the degree of cost stickiness. This study also finds that the degree of asymmetric cost behaviour is more pronounced in the post‐International Financial Reporting Standards (IFRS) period than in the pre‐IFRS period. The results suggest that the increased asymmetric cost behaviour in the post‐IFRS period derives from higher IC efficiency relative to the pre‐IFRS period. This study presents important implications for external stakeholders because they can consider the extent of earnings management constraints and the extent of firms' IC efficiency as the determinants of asymmetric cost behaviour when assessing firms' cost behaviour. Abstract : Examining whether accruals earnings management constraints and intellectual capital (IC) efficiency affect asymmetric cost behavior, this study finds that, on average, when firms experience accruals earnings management constraints in avoiding unfavourable earnings in the current year, they tend to cut slack resources aggressively, leading to increased anti‐sticky cost behaviour. Further, IC efficiency increases the degree of cost stickiness owing to managers' optimistic expectations about sales. Lastly, asymmetric cost behaviour has intensified in the post‐International Financial Reporting Standards (IFRS) period owing to increased IC efficiency after IFRS adoption.